Fungsionalisasi dan Implikasi Asas Kepentingan Terbaik Bagi Anak yang Berkonflik dengan Hukum: Studi Putusan Pengadilan Tinggi Tanjung Karang - Mashuril Anwar; M. Ridho Wijaya (Fakultas Hukum Universitas Jambi, 2019)
The principle of best interest for children requires sanctions of deprivation of liberty as a last resort. Therefore, the principle of the best interests of children must be considered in the resolution of cases of children in conflict with the law. This article, which focuses on the decision of the Tanjung Karang High Court, discusses the functionalization of the best interests principle for children in conflict with the law and the implications of their application. This article concludes, judges in deciding cases of children in conflict with the law in general have not considered the principle of the best interests of the child. Of the 22 cases of children in conflict with the law at the Tanjung Karang High Court in 2011-2016, only three decisions that can be categorized have considered the principle of the best interests of the child. Of the three decisions, two were sentenced not prison and one sentenced to prison. The application of the best interest principle for children in conflict with the law can have both positive and negative implications. It has positive implications, especially for offenders, because it protects children’s rights and reduces the burden of court cases and correctional institutions. But it can also have negative implications, because it is feared not to provide a deterrent effect and invite negative public perceptions of the judiciary. Abstrak Asas kepentingan terbaik bagi anak menghendaki sanksi perampasan kemerdekaan sebagai upaya terakhir. Oleh karenanya, asas kepentingan terbaik bagi anak harus menjadi pertimbangan dalam penyelesaian perkara anak yang berkonflik dengan hukum. Artikel ini, yang berfokus pada putusan Pengadilan Tinggi Tanjung Karang, membahas fungsionalisasi asas kepentingan terbaik bagi anak yang berkonflik dengan hukum dan implikasi penerapannya. Artikel ini menyimpulkan, hakim dalam memutus perkara anak yang berkonflik dengan hukum pada umumnya belum mempertimbangkan asas kepentingan terbaik bagi anak. Dari 22 perkara anak yang berkonflik dengan hukum pada Pengadilan Tinggi Tanjung Karang pada 2011-2016, hanya tiga putusan yang dapat dikategorikan telah mempertimbangkan asas kepentingan terbaik bagi anak. Dari tiga putusan tersebut, dua divonis bukan penjara dan satu divonis penjara. Penerapan asas kepentingan terbaik bagi anak yang berkonflik dengan hukum bisa berimplikasi positif sekaligus negatif. Ia berimplikasi positif terutama bagi pembuat delik, karena melindungi hak-hak anak dan mengurangi beban perkara pengadilan dan lembaga pemasyarakatan. Namun ia juga bisa berimplikasi negatif, karena dikhawatirkan tidak memberikan efek jera dan mengundang persepsi negatif masyarakat terhadap lembaga peradilan.